English Comics To Motivate The Students in Senior High School - Joni; Edward Keith (International Journal of Post Axial: Futuristic Teaching and Learning, 2024)
This research was conducted under the considerations that second year students of Senior High School level need media in teaching-learning process. One of them is English comics in learning English. The objectives of the study were to find out whether there is any significant difference in the motivation of student’s mastery in learning English using comics and without using comics and to identify the effectiveness of English comics as a medium of teaching English. The population of this study was the second-year students of Senior High School Number 17 Takengon. The total number of samples in this study were 32 students. The data were collected through pre-test, post-test and questionnaire. In solving the problems, the researcher carried out an experimental study using statistical method called t-test. The writer used two classes: experiment class and control class. In the control class, the writer used written text story. While in the experiment class, the writer uses English comics. The computation result of t-test was 3.04. the t-table was 2.05 for α=5% and df=34. Because tObs was higher than totable (3.04>2.05), it cloud be concluded that there was significant different in the achievement between the students who were taught using comics and students who were taught without using comics. Referring to the experience in conducting this research, the writer offer suggestion to the teacher to motivate the student’s ability in learning English in order to get better result. The use of comic should be maintained frequently and recommended to English teachers, especially to teach Junior high School’s students in order to attract their motivation in learning English to be more fun.